Implementasi Program Festival Anak Saleh sebagai Upaya Peningkatan Nilai Keislaman Anak oleh Mahasiswa KKN di Desa Aska, Kecamatan Sinjai Selatan - Miranda Wulandari; Fausia Salsabila; Andi Sitti Nurhaliza; A. Muh. Irgi Fatahillah; Asriadi Asriadi (Fakultas Ushuluddin dan Komunikasi Islam, 2026)
The Pious Children's Festival is an educational and religious activity aimed at instilling Islamic values ​​from an early age through various competitions and positive activities, such as Quran memorization, the call to prayer, lectures, and daily worship practices, which are generally organized by educational institutions, mosques, or community organizations. Through a fun and competitive approach, this activity can increase children's interest in learning and practicing religious teachings in their daily lives. In addition, the Pious Children's Festival also plays a role in shaping children's character by instilling the values ​​of honesty, discipline, responsibility, and self-confidence, while developing social skills such as communication and cooperation through interaction with peers. This activity also strengthens the relationship between family, school, and community, because it involves the active participation of parents and teachers in accompanying and motivating children, so that it is not only a competition, but also a means of developing a young generation with noble morals and based on Islamic values.